Long-term complete remission of early hematological relapse after discontinuation of immunosuppressants following allogeneic transplantation for Sezary syndrome - Hiroki Hosoi; Kazuo Hatanaka; Shogo Murata; Toshiki Mushino; Kodai Kuriyama; Akinori Nishikawa; Nobuyoshi Hanaoka; Shinobu Tamura; Hideki Nakakuma; Takashi Sonoki (Hematology Reports, 2018)
Sezary syndrome (SS) is a leukemic form of cutaneous T-cell lymphoma and is chemo-resistant. Allogeneic hematopoietic stem cell transplantation is a promising therapy for SS; however, relapse is common. Therapeutic options after relapse have not been established. We managed an SS patient with hematological relapse within one month after transplantation. After discontinuation of immunosuppressants, she achieved complete remission and remained relapse-free. The chimeric analyses of Tcells showed that the full recipient type became complete donor chimera after immunological symptoms. This clinical course suggested that discontinuation of immunosuppressants may result in a graftversus- tumor effect, leading to the eradication of lymphoma cells.